2002
DOI: 10.1007/bf03027248
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mg−Ni hydrogen storage alloys by rotation-cylinder method

Abstract: For many years, the Mg-Ni alloys have been studied as good lightweight hydrogen storage materials, however, the alloys present strong difficulties in the fabrication process of mass products. The rotation-cylinder method (RCM) has been developed for magnesium based composites with moderate rotation under a normal atmosphere. In this study, the Mg-3, 6, 9, 12 mass%Ni alloys were easily manufactured by RCM and their hydrogenation properties were evaluated with a Sieverts-type automatic pressure-composition-isoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Through the XRD profiles, it is clear that the materials are composed by single phase (MgH 2 ), because Ni acts as catalyst. Hong et al (2002) showed the appearances of the composition of -Mg and the Ni-rich eutectic phase. They observed that the excellent hydrogenation properties and reaction kinetics of the Mg-9 mass% Ni alloy depended on nickel composition, and the -Mg phase acts as a hydrogen storage system and the eutectic structure as the catalytic system.…”
Section: B Hydrogen Sorption Behaviormentioning
confidence: 99%
“…Through the XRD profiles, it is clear that the materials are composed by single phase (MgH 2 ), because Ni acts as catalyst. Hong et al (2002) showed the appearances of the composition of -Mg and the Ni-rich eutectic phase. They observed that the excellent hydrogenation properties and reaction kinetics of the Mg-9 mass% Ni alloy depended on nickel composition, and the -Mg phase acts as a hydrogen storage system and the eutectic structure as the catalytic system.…”
Section: B Hydrogen Sorption Behaviormentioning
confidence: 99%
“…One main disadvantage of ball milling method is that the sample could easily be polluted by steel balls and air, even in very good protection conditions. Other techniques that are usually used to prepare Mg-based materials include melting [2,[13][14][15][16], combustion synthesis [17][18][19], bulk mechanical alloying [20][21][22][23][24], melting spinning [25][26][27][28][29][30], replacement-diffusion method [31], rotation-cylinder [32,33], laser sintering [34], etc.…”
Section: Introductionmentioning
confidence: 99%